Bounded Rationality in Decision Making Under Uncertainty: Towards Optimal Granularity - Lorkowski, Joe; Kreinovich, Vladik (Studies in Systems, Decision and Control,, 2018)
This book addresses an intriguing question: are our decisions rational? It explains seemingly irrational human decision-making behavior by taking into account our limited ability to process information. It also shows with several examples that optimization under granularity restriction leads to observed human decision-making. Drawing on the Nobel-prize-winning studies by Kahneman and Tversky, researchers have found many examples of seemingly irrational decisions: e.g., we overestimate the probability of rare events. Our explanation is that since human abilities to process information are limited, we operate not with the exact values of relevant quantities, but with "granules" that contain these values. We show that optimization under such granularity indeed leads to observed human behavior. In particular, for the first time, we explain the mysterious empirical dependence of betting odds on actual probabilities. This book can be recommended to all students interestedin human decision-making, to researchers whose work involves human decisions, and to practitioners who design and employ systems involving human decision-making -so that they can better utilize our ability to make decisions under uncertainty.